Prostate Anticancer Activity Testing α Mangostin Invitro Study on Sel DU 145 Using WST 8 Method - Rai Chika Dewi; Syafika Alaydrus; Tien Wahyuhandayani (Jurnal Penelitian Pendidikan IPA, 2024)
Prostate cancer is a cancer that has a high risk of death. Prostate cancer, specifically prostate adenocarcinoma, arises from the cells in the prostate gland or its peripheral zone. Chemotherapy, radiation therapy, and surgery are the main treatments for prostate cancer today. Empirical evidence shows that α-mangostin is used as a cancer therapy. At every stage of carcinogenesis, including cell division, proliferation, apoptosis, inflammation, and metastasis, α-mangostin can inhibit it. This study aims to evaluate the activity of α-mangostin against the DU145 prostate cancer cell line, and compare the %survival rate between cisplatin and α-mangostin. The method used is cytotoxicity testing in vitro with the WST-8 method. The research results showed that α-mangostin had an IC50 value of 16.89 ppm, in the active category, IC50 of cisplatin was 4.69 in the active category. Then statistical analysis was carried out using GraphPad Prism versi9.0.0 The results obtained were no significant differences between %survival rate cisplatin and α-mangostin at a concentration of 12.5 ppm. The conclusion of this study is The IC50 values of α-Mangostin and cisplatin against DU 145 cells were 16.89 ppm and 4.65 ppm, respectively. At a concentration of 12.5 ppm, there was no significant difference in their effects.